1997
DOI: 10.1021/ma960940x
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Nonequilibrium Plasma Treatment of Biaxially Oriented Polypropylene

Abstract: The chemical and physical effects incurred at the surface of biaxially oriented polypropylene film during silent discharge plasma treatment have been investigated using XPS, NMR, TOF-SIMS, and AFM techniques. It is found that chain scission accompanied by oxidative attack leads to the formation of low molecular weight oxidized material which agglomerates into globules at the surface due to a large difference in interfacial free energy between the underlying hydrophobic substrate and the oxygenated overlayer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
1
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 40 publications
5
90
1
3
Order By: Relevance
“…In the case of a polypropylene sample highly oxidized by silent electrical discharge treatment, overlapping series of negative ion fragments were observed up to m/z 500. 10 The yields of these fragments tend to be rather low, resulting in poor statistics and problems with accurate mass analysis. However, this problem could be overcome by combining polyatomic primary ion bombardment with the addition of spectra to maintain static SIMS conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of a polypropylene sample highly oxidized by silent electrical discharge treatment, overlapping series of negative ion fragments were observed up to m/z 500. 10 The yields of these fragments tend to be rather low, resulting in poor statistics and problems with accurate mass analysis. However, this problem could be overcome by combining polyatomic primary ion bombardment with the addition of spectra to maintain static SIMS conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, various lowmass oxygen-containing fragments from the ToF-SIMS positive ion spectra were identified as representing the various possible oxygen functionalities seen in the C 1s spectra (these results are discussed below). Boyd et al 10 used ToF-SIMS, XPS and atomic force microscopy (AFM) to study polypropylene oxidized by silent electrical discharge, commenting in particular on the extensive and complex series of negative ions observed. They also used ToF-SIMS to investigate the nature of the removeable lowmolecular-weight oxidized material (by depositing the extract onto silver).…”
Section: Introductionmentioning
confidence: 99%
“…Following the rinsing, neither a mound like structure nor that of a lamella could be observed for the sample treated 200 times. The shape of the globular features (aggregated LMWOM) was explained in terms of the difference in surface energy [58,59]. The LMWOM was easily removed through rinsing with water, due to the fact that it was probably loosely bound to the surface.…”
Section: Nano/micro-surface Topography Modificationmentioning
confidence: 99%
“…It was found that chain scission [59,68,69] accompanied by oxidative attack leads to the formation of low molecular weight oxidized material which agglomerated into globules at the surface. Such low molecular weight fragments of the polymer at the surface acted as a weak boundary layer.…”
Section: Oxidation Mechanism By Flame Treatmentmentioning
confidence: 99%
“…Actually, a simple way to modify the chemical and physical states of the polymer surface, without altering the bulk properties, is by plasma treatment. The plasma treatment of polymers leads to the creation of new chemical groups [5,6], cross-linking and branching of the macromolecules and formation of lowmolecular weight oxidized structures [3,7,8], the rates of these processes being a function of the plasma reactivity. Due to ablation the surface topography of the polymer is affected [9e11].…”
Section: Introductionmentioning
confidence: 99%